Adsorption studies of thiabendazole on peat soil - 465380 Ooi, Wai ni; Wan Aini Wan Ibrahim, supervisor; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2007